Impacts of watershed development programmes: experiences and evidences from Tamil Nadu - Kuppannan, Palanisami; Kumar, D.S. (2009)
The overall performance of watershed development programmes has been examined in the state of Tamil Nadu. The impacts of major watershed development programmes have been outlined in terms of biophysical impacts, environmental impacts, socio-economic impacts and overall economic impacts. It is pointed out that the watershed development activities have made significant positive impacts on various biophysical aspects such as soil and water conservation, soil fertility, soil and water erosion in cropped area, changes in cropping pattern, cropping intensity, production and productivity of crops. Watershed development activities have shown significant positive impacts on water table, perenniality of water in wells, water availability for cattle and other domestic uses, etc. The overall economic impacts have been evaluated in terms of NPV, IRR and BCR. The peoples' participation in watershed development activities has been found satisfactory but the optimal level is yet to be achieved. Training of farmers has been found effective in disseminating technical knowledge. According to the study, the future strategy should be the movement towards a balanced approach of matching the supply-driven menu with a set of demand-driven activities. Peoples' participation, involvement of Panchayati Raj Institutions, local user groups and NGOs along side institutional support from different levels, viz. the Union Government, the state, the district and block levels should be ensured to make the programme more participatory, interactive and cost-effective. Convergence of various rural development programmes around the watershed could be ensured to promote holistic development of watersheds. For its continued success, the programme, should be economically efficient, financially viable, technically feasible and socially acceptable while ensuring equity. For, sustainable development, regular and routine monitoring of environmental parameters is important as environmental enhancement increases the credibility and acceptability of the programme.